Pelatihan Peningkatan Kapasitas Stakeholder dalam Menyusun Strategi City Branding - Mulyasari Agustini, Prima; Widiastuti, Tuti (LPkM Universitas Bakrie, 2020)
Brand is an important concept in the marketing of products, booth goods and services. Giving a city a brand is needed to provide an identity for the city. With a strong brand, a city can